The Semiotics of Contemporary Visual Texts: A Study in New Rhetorical Analysis - Parajuli, Bishwo Raj (Journal of Business and Management, 2018)
This paper explores the semiotics of selected typical visual texts of our time and their implicatures. Some theoretical and conceptual tools for textual interpretation with regards to textual elements exist. However, contemporary visual texts are still prospective area of study. Considering such gap, I have chosen the visual texts that we encounter in our day to day and professional life. For delimitation purposes, only three types of visual communication events have been discussed, selected brochures of academic institutions, selected printed advertisements, and selected billboard advertisements. The analytical tools are predominantly critical discourse of the various motifs, images, structures and persuasive strategies used in the texts. The basic architecture of the discussion part is based on thick descriptions of the textual contents highlighting the semiotics of each. Findings of the study focus on semiotic implications and connotations of the key rhetorical elements. The major finding of the study is most of the visual texts principally try to glorify, glamorize and even exoticize the product or service. The conclusion derived is nothing like absolute conclusion. It is just an array of possible interpretations that pave path for a new discourse like– should we take them for granted? All in all, this is a new rhetorical analysis by outlook.